Firm innovation benefits from regional triple-helix networks. Issue 9 (2nd September 2018) - Elvekrok, Ingunn; Veflen, Nina; Nilsen, Etty R.; Gausdal, Anne H.
ABSTRACT: This study investigates the value of constructed regional triple-helix networks for participating firms. Although participation in such networks is encouraged, the documentation of firm benefits is limited. The results from this longitudinal case study and survey study indicate that the primary benefits from network participation are increased access to knowledge and improved ability to meet challenges. Important characteristics of well-functioning networks are having a committed manager and common activities that build relationships. Lack of resources dedicated to networking limit a firm's outcome, while participating in joint projects enhances it. The study contributes to the literature on network benefits and regional innovation policies.